Motivasi wisatawan mengunjungi desa wisata Blimbingsari, Jembrana, Bali - I Gusti Bagus Rai Utama; I Wayan Ruspendi Junaedi (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study is about tourist’s motivation to visit Blimbingsari Village, Jembrana, in West Bali. This study has aim to determine the push factors, and pulls factors to visit Blimbingsari Village. The respondents are 100 people. Based on their genders, there are 46% male and 54% female. Domestic tourists are 46%, and 28% Australian, and the other nationalities. Student visitors are 28%, 18% are retired, and 64% are workers in various sectors. The result of structural equation modelling (SEM) analysis indicates that the push factor correlation has not significantly affect to the tourist visiting to the Tourism Village of Blimbingsari. The correlations between attractiveness factors have significantly affect to the tourist visiting to the Tourism Village of Blimbingsari. Therefore, the management of Blimbingsari Tourism Village maybe directed to highlight the attractiveness of the village e.g. the uniqueness of the village, the village community activities, culture or traditions, natural beauty of the village, the availability of lodging, culinary, public facilities, visitor center, distance from the airport, the distance from the capital, and availability of transport.